THE ROLE AND IMPORTANCE OF DIDACTIC PRINCIPLES IN ORGANIZING THE EDUCATIONAL PROCESS - B.A. Ismatov (American Journals, 2025)
The issues of improving education management have remained relevant for many years. In recent years, particular attention has been paid to the rational organization of multi-stage education and the development of new-generation educational standards within the context of educational reforms and modernization.This article focuses on the organization and modeling of the educational process, emphasizing the role and importance of didactic principles in this process. It highlights the development of skills and competencies, the integration of individuality and scientificity in education, the systematization of theory and practice, and the regularities of organizational forms.
Keywords: Educational process, modernization, didactic principles, scientificity, individuality, content, methods.